Hubungan Ketersediaan Obat Life-Saving dengan Outcome Pasien Trauma di IGD - Serly Sani Mahoklory; Rosida Rosida (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Background: Trauma is one of the leading causes of death worldwide, especially among people of productive age. Rapid treatment in the emergency department (ED) greatly determines patient outcomes. One important factor is the availability of life-saving drugs, such as adrenaline, tranexamic acid, antibiotics, opioid analgesics, and intravenous fluids. Objective: This study aims to determine the relationship between the availability of life-saving drugs and the outcome of trauma patients in the ED. Methods: This study used an observational analytical design with a cross-sectional approach. The study sample consisted of trauma patients who came to the ED during the study period. The availability of life-saving drugs was measured using a logistics checklist, while patient outcomes were assessed based on initial stabilization status, level of need for further care, and mortality rates. Analysis was performed using the Chi-square test with a 95% confidence level. Results: The results showed a significant relationship between the availability of life-saving drugs and the outcome of trauma patients (p < 0.05). Patients with quick access to life-saving drugs were more likely to stabilize and survive than patients who did not receive immediate medication. Conclusion: The availability of life-saving drugs in the ED is closely related to trauma patient outcomes. Optimizing logistics management and emergency pharmacy availability is very important for improving the quality of ED services. Keywords: Trauma, ED, Life-Saving Drugs, Patient Outcomes ABSTRAK Latar Belakang: Trauma merupakan salah satu penyebab utama kematian di dunia, terutama pada usia produktif. Penanganan cepat di Instalasi Gawat Darurat (IGD) sangat menentukan outcome pasien. Salah satu faktor penting adalah ketersediaan obat life-saving, seperti adrenalin, traneksamat, antibiotik, opioid analgesik, dan cairan intravena.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara ketersediaan obat life-saving dengan outcome pasien trauma di IGD. Metode: Penelitian ini menggunakan desain analitik observasional dengan pendekatan cross-sectional. Sampel penelitian adalah pasien trauma yang datang ke IGD dalam periode penelitian. Ketersediaan obat life-saving diukur menggunakan checklist logistik, sedangkan outcome pasien dilihat berdasarkan status stabilisasi awal, tingkat kebutuhan perawatan lanjutan, serta angka mortalitas. Analisis menggunakan uji Chi-square dengan tingkat kepercayaan 95%. Hasil: Hasil penelitian menunjukkan terdapat hubungan signifikan antara ketersediaan obat life-saving dengan outcome pasien trauma (p < 0,05). Pasien dengan akses cepat terhadap obat-obatan life-saving memiliki kemungkinan lebih besar untuk stabil dan bertahan hidup dibandingkan pasien yang tidak segera mendapat obat. Kesimpulan: Ketersediaan obat life-saving di IGD berhubungan erat dengan outcome pasien trauma. Optimalisasi manajemen logistik dan ketersediaan farmasi emergensi sangat penting untuk meningkatkan kualitas layanan IGD. Kata Kunci: Trauma, IGD, Obat Life-Saving, Outcome Pasien